2020
DOI: 10.3390/ijerph17082969
|View full text |Cite
|
Sign up to set email alerts
|

Can the Psychosocial Safety Climate Reduce Ill-Health Presenteeism? Evidence from Chinese Healthcare Staff under a Dual Information Processing Path Lens

Abstract: Because of heavy workloads, non-transferable responsibilities, and shift systems, healthcare staff are prone to ill-health presenteeism. Based on social information processing theory, this study explored the influence of the psychosocial safety climate (PSC) on ill-health presenteeism. The mediating effects of perceived instrumental support and perceived emotional support and the moderating effect of organic structure in this process were observed. Using a time-lagged research design, data from 386 healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 66 publications
8
20
0
1
Order By: Relevance
“…Our study brings empirical support for this distinction by considering a contextual distal factor, PSC, and a more proximal factor related to job design, psychological demands. Our results are in line with Liu et al (2020) who found that PSC positively predicted the perceptions of the working environment, namely organizational support, which in turn reduced presenteeism. Unlike the present study, which uses a longitudinal design with a representative sample of the population of Québec, Liu et al (2020) use a timelagged design in which not all variables are measured at each time point, and only with a sample of healthcare workers in China.…”
Section: Contributionssupporting
confidence: 92%
See 2 more Smart Citations
“…Our study brings empirical support for this distinction by considering a contextual distal factor, PSC, and a more proximal factor related to job design, psychological demands. Our results are in line with Liu et al (2020) who found that PSC positively predicted the perceptions of the working environment, namely organizational support, which in turn reduced presenteeism. Unlike the present study, which uses a longitudinal design with a representative sample of the population of Québec, Liu et al (2020) use a timelagged design in which not all variables are measured at each time point, and only with a sample of healthcare workers in China.…”
Section: Contributionssupporting
confidence: 92%
“…Our results are in line with Liu et al (2020) who found that PSC positively predicted the perceptions of the working environment, namely organizational support, which in turn reduced presenteeism. Unlike the present study, which uses a longitudinal design with a representative sample of the population of Québec, Liu et al (2020) use a timelagged design in which not all variables are measured at each time point, and only with a sample of healthcare workers in China. Although scholars have proposed a person-focused understanding of the presenteeism behavior (Karanika-Murray and Biron, 2020), the presentee cannot be viewed independently of their work environment and organizational behavior cannot be viewed independently of its context (e.g., Grant et al, 2010;Morgeson et al, 2010).…”
Section: Contributionssupporting
confidence: 92%
See 1 more Smart Citation
“…Liu et al 36 found in their study that low psychosocial safety climate increase ill-health presenteeism. Illhealth presenteeism is defined as the phenomenon of attending work with health problems and places employees in an area between full work engagement and absence from work, thus directly affecting productivity 37 .…”
Section: Discussionmentioning
confidence: 95%
“…This conclusion is consistent with previous studies. Recipients prefer, and usually benefit more from, emotional concern than from cognitive analysis, and emotional support plays an overwhelming role in predicting well‐being (Liu et al., 2020; Longmire & Harrison, 2018).…”
Section: Discussionmentioning
confidence: 99%